Factors Affecting Condition of Styloid Process - Kositbowornchai, Suwadee; Siritapetawee, Mookhda; Weeraarchakul, Wilawan (Khon Kaen University Dental Journal, 2019)
The aim of the current study was to evaluate the condition of the styloid process in dental patients and analyze the factors that might be affecting the mineralized condition of the styloid process. Three hundred digital panoramic radiographs were retrieved from the X-ray data of dental patients who received at least one dental treatment between October and December, 2016. Five factors (including sex, age, tooth status, pulp stone, and side) were recorded vis-à-vis the condition of the styloid process. These were then divided into 11 forms (labelled “a” to “k”). Conditions “a” to “d” were categorized as normal styloid processes. Condition “e” represented an elongated styloid process. Conditions “f” to “k” were calcified stylohyoid ligaments. Two observers cooperated in each radiograph evaluation. Descriptive analyses were done for each condition and each variable. The relationship between each factor was analyzed using a multiple logistic regression. Among the conditions classified, type “d” was found most in both sides, 109 (36.3%) in the right side and 125 (41.7%) in the left. The mean age was 35.42±18.52 years (range, 18-88). The female to male split was 207 (69%) to 93 (31%). Females presented normality of the styloid process on the right side 1.99 times more than males (95% CI =1.01-3.93, p=0.048). There was no significant difference in the condition of the styloid process vis-à-vis age. The number of missing teeth ranged between 0 and 32 teeth in 219 patients (73%). There was no significant difference between dentulous and edentulous patients (p=0.08). Pulp stones occurred in 64 cases (21.3%). The persons who presented a normal left styloid process also presented a normal right styloid process more than any other condition (p<0.0001). In conclusion, the “d” styloid process condition was found most on both sides. The condition and number of styloid processes on the right side differs from the contralateral side. Sex and the side are associated with the styloid process and stylohyoid ligament classification.